Voltammetric Sensing of Bilirubin Based on Nafion/Electrochemically Reduced Graphene Oxide Composite Modified Glassy Carbon Electrode - Aslıhan Avan, Asiye; Aydar, Sevda; Filik, Hayati (Current Analytical Chemistry, 2015)
A sensitive square wave voltammetric sensor for the quantification of bilirubin (BR) at the Nafion-electrochemically reduced graphene oxide (NF/ER-GO) hybrid composite modified conventional glassy carbon electrode was offered. The voltammetric oxidation conducts of bilirubin at the NF/ER-GO modified GC electrode were examined in acetone containing H&2SO4 as the supporting electrolyte. The electrochemical conduct of BR on NF/ER-GO hybrid modified GC electrodes was explored by electrochemical impedance spectroscopy, cyclic voltammetry and square-wave voltammetry (SWV). The oxidation peak current response of BR achieved at the NF/ER-GO modified GC electrode was 3 times higher than that of the unmodified GC electrode. At specified conditions, the linear calibration curve for BR showed two good linear segments: the first linear segment increased from 2.0 μM to 20 μM and second linear segment increased up to 70 μM. The limit of detection was calculated as 0.84 μM using SWV. The results showed that the NF/ER-GO modified electrode can be applied to determine BR without interference from ascorbic acid and uric acid, while ensuring good sensitivity, selectivity, and reproducibility. Finally, the proposed sensor was successfully employed to detect bilirubin in human serum samples.
Keywords: Bilirubin